Activation of CD35 and CD55 in HIV associated normal and pre-eclamptic pregnant women. (September 2016) - Khan, R.; Maduray, K.; Moodley, J.; Naicker, T.
Abstract: Objective: The delicate balance which exists between complement activation and its regulation is altered in HIV infection and pregnancy disorders such as pre-eclampsia. Therefore, the purpose of this study was to investigate the expression of complement regulatory (Creg) proteins (CD35 and CD55) in HIV associated normal and pre-eclamptic pregnancies. Study design: The total study population ( n = 100) consisted of normotensive pregnant ( n = 50) and pre-eclamptic ( n = 50) women. These groups were equally sub-stratified into HIV infected and uninfected groups ( n = 25 per group). Standard haematological tests were conducted. Flow cytometric analysis of isolated neutrophils were performed using fluorescein isothiocyanate-conjugated anti-CD35 and phycoerythrin-cyanine 5 conjugated anti-CD55. Results: HELLP syndrome characteristics of increased lactate dehydrogenase enzymes levels, low platelet counts, cell morphological abnormalities (red cell fragmentation) and anaemia were observed in 40% of the HIV infected pre-eclamptic group. Red cell fragmentation inclusive of burr cells and schistocytes were also noted. Activated partial thromboplastin time and fibrinogen differed significantly between the HIV uninfected pre-eclamptic compared to the HIV infected pre-eclamptic groups ( p < 0.01). Irrespective of HIV status, the mean fluorescence intensity of CD35 and CD55 were significantly higher in the pre-eclamptic compared to the normotensive pregnant ( p = 0.0001; p = 0.0001 respectively) groups. In the pre-eclamptic groups, the expression of both CD35 and CD55 did not significantly differ between HIV infected and uninfected women ( p = 0.486; p = 0.767 respectively). Conclusions: This study demonstrates an up-regulation of complement regulatory proteins, CD35 and CD55 in HIV associated pre-eclamptic compared to normotensive pregnancy. This elevation of the Creg proteins is an adaptive immune response to the high complement-mediated cell lysis that occurs in HIV infection and further aggravated by the complement activated state of pre-eclampsia.